(untitled) (Journal of Enam Medical College, 2023)
Background: Tinea cruris constitutes a major health problem worldwide. Although not lifethreatening, it can cause significant discomfort in daily activities. So, search for better therapeutic options in terms of clinical efficacy and safety profile is ongoing. Objective: To compare the efficacy and safety of topical terbinafine 1% and butenafine 1% cream in the treatment of tinea cruris. Materials and Methods: This Comparative interventional study was carried out in the Dermatology & Venereology department of Bangabandhu Sheikh Mujib Medical University between October 2014 and March 2015. A total of 50 patients of tinea cruris who met the inclusion criteria and provided consent were enrolled in the study. They were then divided into two groups as Group A (terbinafine group) and Group B (butenafine group) in a 1:1 ratio following a simple randomization method. Patients were advised to apply the medication once daily for 2 weeks and evaluated on the basis of clinical assessment score at the end of 1 and 2 weeks. Results: The baseline socio-demographic characteristics of the two groups were not statistically significantly different. Higher clinical cure was observed in butenafine recipients as compared with terbinafine recipients on the basis of mean clinical assessment score at the end of 7 days (5.72±0.7 vs 4.12±0.7) and 14 days (3.04±0.5 vs 1.44±0.9). The difference was statistically significant at both the time points. Both the drugs were well-tolerated except one patient of terbinafine group complained of transient burning. Conclusion: Treatment with butenafine 1% cream can be considered superior to terbinafine 1% cream in case of tinea cruris. J Enam Med Col 2021; 11(1): 39-46